Mexico, nation in transit : contemporary representations of Mexican migration to the United States - Sisk, Christina L., 1974- (University of Arizona Press, 2011)
"This book argues for a deterritorialized notion of Mexican national, regional, and local identities by analyzing the representations of migration within Mexican and Mexican American literature, film, and music from the last twenty years"--Provided by publisher.